Structural stability and mass transfer properties of pressure retarded osmosis (PRO) membrane under high operating pressures - Li, Ye (2015)
The fabrication of new membrane that is able to produce stable high power density is essential for the development of pressure retarded osmosis (PRO) technology. In this work, thin film composite (TFC) polyetherimide membranes with three different substrate structures were fabricated and characterized. The PRO performance of the resultant membrane was evaluated through two pressure cycle experiments and stability tests. The primary objective of this work is to systematically study PRO membrane’s mechanical stability and mass transfer properties under high operating pressures, which determine the power density of the membrane in the PRO process. Experiments revealed that water permeability (Ap) and salt permeability (Bp) under different pressures varied. The Ap and Bp are better indicators for examining the variation of PRO membrane structure under pressure. Within the operating pressure range of 17.2 bar, the top polyamide layer of TFC PEI-2# membrane mainly experienced a reversible deformation. In the two pressure cycle tests, the water flux, specific salt flux and power density obtained in the upward and downward measurements in each cycle are close to each other. The first cycle and the second cycle also show excellent reproducibility. The membrane was able to maintain almost unchanged water flux and power density of 12.8 W/m2 at 17.2 bar over the 10 h testing time, suggesting the membrane’s great potential to be used in practical application in the future.